The Legal Environment of Advertising in Ukraine - Bulat, Nataliia (Teisė, 2022)
The legal environment of advertising in Ukraine is addressed in the article. The research results are based on the study of legal regulation of relations in the field of advertising and the examination of the legal relations in this field with regard to classical consideration of three elements of legal relations – subjects, objects and content. The author clarifies a classification of legal acts regulating relations in the field of advertising, determines subjects of relations in this field and gives their classification, proposes criteria for a classification of advertising and provides this classification, and describes the content of relations in the field of advertising.
Keywords: advertising; legislation in the a field of advertising; legal relations in the field of advertising; advertising producer; advertising disseminator; advertiser; advertising consumers